Defective p53 antiangiogenic signaling in glioblastoma - Berger, Benjamin; Capper, David; Lemke, Dieter; Pfenning, Philipp-Niclas; Platten, Michael; Weller, Michael; Deimling, Andreas von; Wick, Wolfgang; Weiler, Markus (Neuro-Oncology, 2010)
Previous findings suggest an angiogenesis-regulating function of the p53 tumor suppressor protein in various malignancies. With several antiangiogenic agents entering the clinic, we assessed the value of the TP53 status in predicting angiogenesis in glioblastoma in vivo and examined underlying angiogenic-signaling pathways in vitro. We identified 26 TP53 wild-type and 9 TP53 mutated treatment-naïve, primary, isocitrate dehydrogenase 1 (IDH1) wild-type glioblastoma specimens by sequence analysis and quantified vascularization. P53 responsiveness of the angiogenesis-related target genes, such as vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), thrombospondin 1 (TSP-1), brain-specific angiogenesis inhibitor 1 (BAI1), and collagen prolyl-4-hydroxylase alpha 2 (P4HA2), was evaluated by (i) overexpression of wild-type p53 in homozygously TP53-deleted LN-308 cells; (ii) shRNA-mediated p53 knockdown in the TP53 wild-type LNT-229 cells; and (iii) chemical induction of wild-type p53 expression in LNT-229 cells by camptothecin. Irrespective of the TP53 status, vascularization did not differ significantly between the two groups of glioblastoma specimens. Of all target genes, only P4HA2 mRNA was upregulated through wild-type p53. As opposed to several nonglial tumors, in glioblastoma cells, p53-mediated transcriptional induction of P4HA2 mRNA neither resulted in increased levels of P4HA2 protein or antiangiogenic endostatin nor did it influence endothelial cell sprouting, viability, or transmigration in vitro. Moreover, p53-uncoupled stable overexpression of P4HA2 in LN-308 cells did not affect endothelial cell viability. These data challenge the view of p53 as an angiogenesis-regulator in glioblastoma in that relevant signaling pathways are silenced, potentially contributing to the angiogenic switch during malignant progression.
Gesehen am 18.01.2023